Lutzomyia (L.) longipalpis (vetor da Leishmaniose Visceral Americana): a competência vetorial à diferentes espécies de Leishmania e a diversidade da microbiota - Ana Clara Araújo Machado Pires (2018)
Studies of the interaction between Leishmania protozoans with phlebotomine vector constitute an important field of research, since it can improve our knowledge of the processes involved in the transmission of the parasite and the epidemiology of Leishmaniasis. Details regarding all of the aspects between parasite-vector interaction are desirable for a formulation of novel protozoan and vector control strategies. Some phlebotomine species show remarkable specificity for exclusive vectors of certain Leishmania species transmitted in nature, while other species may be experimentally infected by more than one species of parasite. The term "Permissive Vectors" has been created to describe the latter. It is not yet known exactly how the interaction between Permissive Vectors with the Leishmania parasites works, but it is hypothesized that the mechanism of adhesion within the midgut of these vectors differs from the "Natural Vectors". The present study describes the development of five distinct species of Leishmania - L. (Leishmania) infantum chagasi, L. (Leishmania) major, L. (Leishmania) amazonensis, L. (Leishmania) mexicana and L. (Viannia) braziliensis - in Lutzomyia (L.) longipalpis, considered, experimentally, a permissive vector. Different concentrations of parasites were required for determination of vector permissibility. Our results showed that the ability of Lu. (L.) longipalpis from being infected experimentally by Leishmania is dose dependent and the vector proved to be competent to transmit L. (L.) major and L. (L.) mexicana.